Engineering Solutions for Climate-Conscious Cultivation: Solar Energy's Role in Enhancing Agricultural Productivity in Punjab - Ghalib Nadeem; Dr. Muhammad Khalid; Dr. Kamran Raza; Abdul Khaliq (Spectrum of Engineering Sciences, 2024)
The study investigates the use of solar energy and project management in the sustainable agriculture sector of Punjab, Pakistan. A 40-acre land with a solar-powered water reservoir supports up to 15-17 irrigation sets, demonstrating a strategic combination of reserve management and environmental stewardship. The agronomy of Onions, Cauliflower, Cucumber, and Brinjal on the farm could yield a profit between 6.99 and 7.23 million Rupees, with a breakeven point of 5 to 6 months. This model demonstrates profitable, eco-friendly agronomic practices, addressing water insufficiency and climate effect challenges. The research highlights the need for specific project management to fully utilize solar-powered tube wells for irrigation systems and set a precedent for future agronomy activities. Additionally, the research emphasizes the importance of implementing efficient water usage techniques and incorporating sustainable farming methods to mitigate the impact of climate change on agricultural productivity. By prioritizing the use of solar-powered tube wells for irrigation, the farm not only reduces its carbon footprint but also sets a positive example for other agricultural operations to follow suit. Overall, this model showcases the potential for profitable farming practices that prioritize environmental sustainability and resource management. Keywords: Agricultural Sector Punjab, Carbon footprint, Solar Energy.